Comparing the effectiveness of emotion regulation training and metacognitive therapy on social-emotional adjustment and dysfunctional thoughts in men with substance abuse treated with methadone - Elham Alizadeh; Fathollah Mohammadian; Shahram Mami (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām)
Introduction:  Drug addiction is a significant obstacle to society's growth and humanity's flourishing, posing significant health and efficiency risks for the current generation. The present study aimed to compare the effectiveness of emotion regulation training and metacognitive therapy on emotional-social adjustment and dysfunctional thoughts in men with substance abuse undergoing methadone treatment. Materials & Methods: This study was a quasi-experimental study that consisted of addicts undergoing methadone treatment who were referred to all addiction treatment clinics in Ilam in 2020. In accordance with the inclusion criteria, 60 people were selected through purposive sampling and randomly divided into three groups of 20 people (two experimental groups and one control group). Bell's Emotional-Social Adjustment Questionnaire and Beck and Wiseman's Dysfunctional Thoughts Questionnaire were used to collect data. The control group didn’t receive any intervention, but the first experimental group received emotion regulation training interventions in 8 120-minute sessions, and the second experimental group received metacognitive therapy interventions in 8 90-minute sessions in a one-on-one and group setting. The research data were analyzed using analysis of covariance in SPSS V.23 at the significance level of 0.05. Results: There was a significant difference in the variables of emotional-social adjustment and dysfunctional thoughts in the post-test phase between the groups (p<0.001). There was no significant difference in the variables of emotional-social adjustment and dysfunctional thoughts between the two trainings (P>0.05). Conclusion: It seems that both trainings increased emotional-social adjustment and reduced dysfunctional thoughts in men with abuse, but metacognitive therapy was more effective.